MAIN REQUIREMENTS FOR A POSTICHE WORKSHOP - Feruza Suratovna Djalilova (Web of Journals Publishing, 2025)
This article discusses the requirements for a postiche workshop, safety regulations, the work process of wigmakers, and the set of tools and equipment necessary for performing postiche (wig-making) work.
Keywords: Hairpiece, makeup, curling irons, card, scissors, brush, hook, electric curling iron, tape measure, thick black pencil, pin, dovite, razor, tressbank curlers, headpiece, headpiece stand.